2015
DOI: 10.1039/c5ta01106j
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of SnOx nanocrystalline aggregates encapsulated by amorphous TiO2 as an anode in Li-ion battery

Abstract: SnO x nanocrystalline aggregates (NAs) encapsulated by an amorphous TiO 2 layer have been successfully designed by a one-step flame spray pyrolysis (FSP). The synthesized SnO x NAs@TiO 2 with different degrees of aggregations were composed of SnO x nanocrystallites ranging from 5 nm to 10 nm and a TiO 2 layer with a thickness of 1-5 nm. The encapsulated TiO 2 layer was introduced in situ by incorporating TiCl 4 into the downstream of an FSP reactor, where TiO 2 nucleated and grew in the surface of the SnO x NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 41 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…Moreover, the first scan on the negative-current side have a broad reduction peak in the range of 0 to 1.25 V. Compared with the following scans, these irreversible peaks are mainly attributed to the formed solid electrolyte interphase (SEI) films. 20,21,36 These observed peaks further confirmed that the electrochemical reaction takes place in a multistage process with active TiO 2 and MoO 3 components. Fig.…”
Section: Electrochemical Performancesupporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, the first scan on the negative-current side have a broad reduction peak in the range of 0 to 1.25 V. Compared with the following scans, these irreversible peaks are mainly attributed to the formed solid electrolyte interphase (SEI) films. 20,21,36 These observed peaks further confirmed that the electrochemical reaction takes place in a multistage process with active TiO 2 and MoO 3 components. Fig.…”
Section: Electrochemical Performancesupporting
confidence: 58%
“…21,31 These components were mixed and stirred into slurry with N-methyl-2pyrrolidone (NMP) and uniformly pasted on Cu foils (19 µm) with a membrane thickness of 50 µm. The average loading mass of active materials have an average value of 0.52 mg/cm 2 (the area of used Cu foils is 1.44 cm 2 ).…”
Section: Electrochemical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical yolk‐shell structure, surface of the shell structure forms a stable solid electrolyte interface while the yolk part of the structure shrinks and expands without forming a solid electrolyte interface. Moreover, even if the active electrode material as the yolk structure pulverizes during the intercalation processes, the components will be kept within the structure and will continue to provide electrical contact …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even if the active electrode material as the yolk structure pulverizes during the intercalation processes, the components will be kept within the structure and will continue to provide electrical contact. [9][10][11][12][13][14][15][16] Several research studies have proposed a very thin layer of carbon over the surface of active electrode materials by using hydrocarbons such as glucose, and these approaches have been successfully applied to various electrode materials in the field of Li-ion batteries. However, thin carbon layers over the active electrode materials could accommodate the mechanical stresses in a limited extent because the layer disintegrates in each cycle if the core electrode suffers severely from large volumetric changes.…”
Section: Introductionmentioning
confidence: 99%